Factors that contribute customers’ preference in selecting a restaurant / Nur Atikah Abdul Rahman and Nur Syakirah Che Norazman - Abdul Rahman, Nur Atikah; Che Norazman, Nur Syakirah (2018)
There are a lot of restaurants in Malaysia. According to Department of Statistics Malaysia (2015), there were 167,490 establishments of food and beverage services in Malaysia. In Malaysia, for sure, you will never run out of ideas to find the right restaurant whether street foods, fancy restaurants, mamak stalls or fast food restaurants (Sin, 2017). Malaysia also called as a food heaven for a reason (Sin, 2017). There are different types of restaurant which have different factors that can contribute customers in selecting the restaurant.